Educational Aspiration and Cultural Capital: The Indispensable Factors of Educational Attainment in Kerala - Aswathi Kunjumon
ocial disparity referred to as social differences that continue within each sector of the society. The paper highlights the linkage between disparity in educational attainment and the role of cultural capital towards the aspiration for education. Educational outlook and exposure can be varied depending on certain factors like the location where they reside, education and occupation of parents, socioeconomic status of the family, and amenities provided by schools. The overriding factors which contribute towards educational aspiration are the parental education and occupation. As education is the leading facet for an individual towards their expectations for existence, these factors bring constructive and unconstructive outputs. Pierre Bourdieu (1998) argues that individuals are endowed with durable cognitive structures and a dispositional sense of action that directs them to appropriate responses to given situations, which refers to as cultural capital, i.e., the familiarity of prestigious aesthetic culture, such as high arts, literary culture and linguistic ability which helps the individual to make comfortable in the formal school setting. It was found that in Kerala, the most influential cultural capital which added advantage to the basic education is the parental occupation rather than literary culture, and linguistic ability. It lessens the true picture that, a new emerging society of Kerala lacks the value of literary wealth as part of the commercialization of education. The Higher secondary students (final years of basic education) were the respondents, and the samples are drawn from rural, semi-urban and urban areas of Ernakulam district, Kerala using interview schedule.